PLK1 protects intestinal barrier function during sepsis by targeting mitochondrial dynamics through TANK-NF-κB signalling - Ying-Ya Cao; Yuan Zhang; Wuyun Gerile; Yan Guo; Li-Na Wu; Li-Li Wu; Kai Song; Wei-Hua Lu; Jian-Bo Yu (BMC, 2022)
Abstract Background Intestinal barrier integrity in the pathogenesis of sepsis is critical. Despite an abundance of evidence, the molecular mechanism of the intestinal barrier in sepsis pathology remains unclear. Here, we report a protective role of polo-like kinase 1 (PLK1) in intestinal barrier integrity during sepsis. Methods Mice with PLK1 overexpression (CAG-PLK1 mice) or PLK1 inhibition (BI2536-treated mice) underwent caecal ligation and puncture (CLP) to establish a sepsis model. The intestinal barrier function, apoptosis in the intestinal epithelium, mitochondrial function and NF-κB signalling activity were evaluated. To suppress the activation of NF-κB signalling, the NF-κB inhibitor PDTC, was administered. The Caco-2 cell line was chosen to establish an intestinal epithelial injury model in vitro. Results Sepsis destroyed intestinal barrier function, induced excessive apoptosis in the intestinal epithelium, and disrupted the balance of mitochondrial dynamics in wild-type mice. PLK1 overexpression alleviated sepsis-induced damage to the intestinal epithelium by inhibiting the activation of NF-κB signalling. PLK1 colocalized and interacted with TANK in Caco-2 cells. Transfecting Caco-2 cells with TANK-SiRNA suppressed NF-κB signalling and ameliorated mitochondrial dysfunction, apoptosis and the high permeability of cells induced by lipopolysaccharide (LPS). Furthermore, TANK overexpression impaired the protective effect of PLK1 on LPS-induced injuries in Caco-2 cells. Conclusion Our findings reveal that the PLK1/TANK/NF-κB axis plays a crucial role in sepsis-induced intestinal barrier dysfunction by regulating mitochondrial dynamics and apoptosis in the intestinal epithelium and might be a potential therapeutic target in the clinic.